Problem Based Learning in Cooperative Situation (PBLCS) and Its Impact on Development of Personal Intelligence - Ahmad Talib; Ismail bin Kailani (Institute of Advanced Engineering and Science, 2014)
The objective of this study was focused on the observation on the practice of PBLCS learning model, and its impact on the development of personal intelligence (interpersonal and intrapersonal) students. This study used a quasi-experimental design with one factor measurement. The study population was students of class XI, IPA (Natural Science) SMAN (Senior High School) 22 in Makassar City, including 6 top schools and 16 regular schools, in the second semester in the period 2012/2013. The sample of this study included both one top school and two regular schools using a random sampling technique. Based on the sample selection technique, two classes were selected from the top school; SMAN 1 and two classes from regular classes; SMAN 4, and SMAN 18, involving 103 students for PBLCS and 103 students for PT (traditional class). Data of this study were analyzed inferentially and descriptively, inferential analysis using multivariate statistic and a multivariate analysis using variance or one-way MANOVA. The results of this study showed that the implementation of PBLCS model (treated class) was better than the PT strategy (controlled class) in developing personal intelligence of students, with the significance 0.000 <α = 0.05. It was supported by descriptive data indicating that the mean score of personal intelligence development. Both interpersonal and intrapersonal intelligence of students in the treated class was higher than the development of interpersonal or intrapersonal intelligence students in the controlled class.DOI: http://dx.doi.org/10.11591/ijere.v3i4.6969